Rapid screening of nine illicit drugs in human blood and urine by direct analysis in real-time mass spectrometry - Ying Zhang; Wenfang Zhang; Guobin Xin; Li Liu; Xiaokun Duan; Charles Liu (Wolters Kluwer Medknow Publications, 2019)
We aimed to establish for the rapid detection of morphine, O6-monoacetylmorphine, heroin, codeine, cocaine, methamphetamine, ketamine, methadone, and dolantin in human blood and urine by direct analysis in real-time coupled with tandem mass spectrometry (DART-MS/MS). These samples were extracted by acetonitrile-methanol (V/V = 4:1), using DART 12 Dip-it automatic sampling system. They were injected at 400°C, and analyzed by positive ion and multiple reaction monitoring mode. The detection limits of morphine, O6-Monoacetylmorphine, heroin, codeine, cocaine, methamphetamine, ketamine, methadone, and dolantin were 100, 50, 50, 100, 20, 20, 10, 1, and 0.01 ng/mL, respectively. The practical cases contained methamphetamine, codeine, cocaine, and O6-monoacetylmorphine were detected accurately and rapidly. The method has the advantages of high sensitivity and good accuracy. The sample processing is simple and can be analyzed in a short time. This method is suitable for the analysis of morphine, O6-monoacetylmorphine, heroin, codeine, cocaine, methamphetamine, ketamine, methadone, and dolantin in some practical cases.